Flexible PVDF/Cu/PVDF-NaNbO3 photoanode with ferroelectric properties: An efficient tuning of photoelectrochemical water splitting with electric field polarization and piezophototronic effect. (December 2017) - Singh, Simrjit; Khare, Neeraj
Abstract: Piezophototronic effect and electric field polarization using ferroelectric-semiconductors are recently discovered phenomena for realizing efficient photoelectrochemical (PEC) water splitting. However, conventionally semiconductor materials deposited on rigid and mechanically brittle (Si, FTO and ITO) substrates have been used as photoelectrodes which hinder the scalability of PEC technology. Herein, we introduce a facile and economically feasible approach for the fabrication of flexible and scalable photoelectrodes with ferroelectric properties for efficient PEC water splitting. A flexible PVDF/Cu/PVDF-NaNbO3 photoanode using ferroelectric-semiconducting PVDF-NaNbO3 film on flexible PVDF/Cu substrate is fabricated and an enhancement in the water oxidation performance of ~121% with electric field polarization is demonstrated. A positively poled photoanode exhibits the highest photocurrent (~1.37 mA/cm 2 ) compared to as-prepared photoanode (~0.72 mA/cm 2 ) and negatively poled photoanode (~0.62 mA/cm 2 ). Moreover, due to flexibility and piezoelectric properties of PVDF/Cu/PVDF-NaNbO3 photoanode, a further enhancement in the photocurrent ~26% is obtained using the piezophototronic effect. Our present approach of fabricating flexible ferroelectric-photoelectrodes with tunable PEC properties will pave the way for constructing high performance commercial PEC systems. Graphical abstract: Highlights: Fabricated flexible and scalable PVDF/Cu/PVDF-NaNbO3 photoelectrode with ferroelectric properties. Demonstrated electrical polarization and piezo-phototronic effect induced enhancement in the PEC properties. PVDF/Cu/PVDF-NaNbO3 photoanode exhibits ~121% enhancement in the photocurrent with electric field polarization. PVDF/Cu/PVDF-NaNbO3 photoanode exhibits ~26% enhancement in the photocurrent using the piezophototronic effect. An approach towards fabricating PEC systems for commercial applications.